Improving urban drainage systems to mitigate PPCPs pollution in surface water: A watershed perspective - Zhao, Xue; Zheng, Yi; Hu, Shiyao; Qiu, Wenhui; Jiang, Jiping; Gao, Chuanzi; Xiong, Jianzhi; Lu, Haiyan; Quan, Feng (Journal of hazardous materials, 2021)
Parabens are preservatives widely used in pharmaceutical and personal care products (PPCPs). This study investigated urban water pollution by parabens from a watershed perspective. Water and sediment samples were collected from one of the most polluted urban streams in China. Six parabens and five paraben metabolites were frequently detected in the samples, whereas the overall pollution level was intermediate according to a global comparison. The spatial distributions of the chemical concentrations along the river are influenced by multiple factors, and WWTPs appear to be a major factor. In general, the target pollutants were detected at higher concentrations in the dry season than in the wet season, but extraordinary concentration peaks in water were observed downstream of wastewater treatment plants (WWTPs), indicating a dominant contribution from combined sewage overflows (CSOs) during rainfall events. In a representative WWTP-influenced reach, CSOs account for its 97.3% of ∑parabens input and 96.9% of ∑metabolites input in a typical rainfall event. Converting the existing combined sewer systems to separate stormwater drainage systems could reduce the inputs of ∑parabens and ∑metabolites by 86.9–84.5%, respectively. This study highlights the role of urban drainage systems in preventing surface water pollution by PPCPs. Urban drainage systems play a critical role in controlling pollution by parabens and their metabolites in urban surface water. [Display omitted] •Transport of parabens in urban surface water was investigated at a watershed scale.•The occurrence of five paraben metabolites in Chinese rivers was first reported.•CSOs contributed over 95% of the chemicals input to the river in the rainfall event.•The new drainage systems avoid CSOs and may reduce over 80% of the chemicals input.